Current Worldwide Trends in Pediatric Helicobacter pylori Antimicrobial Resistance - Reka Borka Balas; Lorena Elena Meliț; Cristina Oana Mărginean (MDPI AG, 2023)
Helicobacter pylori (H. pylori) has acquired several resistance mechanisms in order to escape the currently used eradication regimens such as mutations that impair the replication, recombination, and transcription of DNA; the antibiotics capability to interact with protein synthesis and ribosomal activity; the adequate redox state of bacterial cells; or the penicillin-binding proteins. The aim of this review was to identify the differences in pediatric H. pylori antimicrobial-resistance trends between continents and countries of the same continent. In Asian pediatric patients, the greatest antimicrobial resistance was found to metronidazole (>50%), probably due to its wide use for parasitic infections. Aside from the increased resistance to metronidazole, the reports from different Asian countries indicated also high resistance rates to clarithromycin, suggesting that ciprofloxacin-based eradication therapy and bismuth-based quadruple therapy might be optimal choices for the eradication of H. pylori in Asian pediatric population. The scarce evidence for America revealed that H. pylori strains display an increased resistance to clarithromycin (up to 79.6%), but not all studies agreed on this statement. Pediatric patients from Africa also presented the greatest resistance rate to metronidazole (91%), but the results in terms of amoxicillin remain contradictory. Nevertheless, the lowest resistance rates in most of the African studies were found for quinolones. Among European children, the most frequent antimicrobial resistance was also noticed for metronidazole and clarithromycin (up to 59% and 45%) but with a predominance for clarithromycin as compared to other continents. The differences in antibiotic use among continents and countries worldwide is clearly responsible for the discrepancies regarding H. pylori antimicrobial-resistance patterns, emphasizing the crucial role of global judicious antibiotic use in order to control the increasing resistance rates worldwide.